Tudo que nóis tem é nois: a democracia cultural como eixo norteador nas ações culturais e desenvolvimento da economia criativa e turismo cultural na cidade de Ponta Grossa/PR - (:unkn) unknown (Universidade Estadual de Ponta Grossa, 2025)
Culture is not always seen as a right. But it is a constitutional right. Everyone has the right to access, produce, and enjoy cultural goods and services within the national territory. This thesis aims to demonstrate that the city of Ponta Grossa/PR has the means to apply Cultural Democracy in favor of the Creative Economy and Cultural Tourism, as a way to ensure the social, economic, and cultural development of the community. To this end, the research is divided into four chapters: the first is devoted to the conceptualization of Cultural Democracy and its difference from Cultural Democratization; the second addresses the concepts of Creative Economy and Cultural Tourism and their relationship with Cultural Democracy; the third presents the municipality of Ponta Grossa/PR, its events, and an analysis of the actions promoted by the public authorities in line with the concept of Cultural Democracy; and the fourth chapter features interviews with the municipal administration and actors in the cultural scene of Ponta Grossa, with their demands, interests, arguments, and experiences with the events and public notices of the Municipal Secretariat of Culture. In terms of methodology, the chapters were written using Method Triangulation, drawing on bibliographic and documentary sources, the hypothetical-deductive method, and semi-structured interviews with public managers and actors involved in the development of cultural policy in the municipality of Ponta Grossa. Among the authors used for theoretical argumentation are: Pierre Boudieu, Start Hall, Norberto Bobbio, Zygmunt Bauman, Hannah Arendt, Marilena Chaui, and John Howkins. It is clear that the cultural actions promoted by the Municipal Secretariat of Culture do not fully embrace the concept of Cultural Democracy, despite the attempts of the public authorities, and the main issue lies in the State acting as the executor of actions rather than as a manager/mediator. This hinders social participation and, consequently, the other elements of the concept. Open innovation techniques and public-private partnerships may be the way forward.
Keywords: Democracia cultural; Economia criativa; Turismo cultural; Desenvolvimento regional; Ciências Sociais Aplicadas